Cochlear implants: Insertion assessment by computed tomography - Menegatti Pavan, Ana Luiza [UNESP]; Alves, Allan Felipe Fattori [UNESP]; Giacomini, Guilherme [UNESP]; Altemani, João Maurício Carrasco; Castilho, Arthur Menino; Lauria, Raquel Andrade; da Silva, Vagner Antonio Rodrigues; Guimarães, Alexandre Caixeta; de Pina, Diana Rodrigues [UNESP] (Elsevier, 2018)
Background and objectives: Imaging exams play a key role in cochlear implants with regard to both planning implantation before surgery and quality control after surgery. The ability to visualize the three-dimensional location of implanted electrodes is useful in clinical routines for assessing patient outcome. The aim of this study was to evaluate linear and angular insertion depth measurements of cochlear implants based on conventional computed tomography. Methods: Tools for linear and angular measurements of cochlear implants were used in computed tomography exams. The tools realized the insertion measurements in an image reconstruction of the CIs, based on image processing techniques. We comprehensively characterized two cochlear implant models while obviating possible changes that can be caused by different cochlea sizes by using the same human temporal bones to evaluate the implant models. Results: The tools used herein were able to differentiate the insertion measurements between two cochlear implant models widely used in clinical practice. We observed significant differences between both insertion measurements because of their different design and construction characteristics (p = 0.004 and 0.003 for linear and angular measurements, respectively; t-test). The presented methodology showed to be a good tool to calculate insertion depth measurements, since it is easy to perform, produces high-resolution images, and is able to depict all the landmarks, thus enabling measurement of the angular and linear insertion depth of the most apical electrode contacts. Conclusion: The present study demonstrates practical and useful tools for evaluating cochlear implant electrodes in clinical practice. Further studies should measure preoperative and postoperative benefits in terms of speech recognition and evaluate the preservation of residual hearing in the implanted ear. Such studies can also determine correlations between surgical factors, electrode positions, and performance. In addition to refined surgical techniques, the precise evaluation of cochlear length and correct choice of cochlear implant characteristics can play an important role in postoperative outcomes.
Keywords: Cochlear implants; Computed tomography; Image reconstruction; Insertion measurements